Positioning the Red Deer (Cervus elaphus) Hunted by the Tyrolean Iceman into a Mitochondrial DNA Phylogeny - Olivieri, Cristina; Marota, Isolina; Rizzi, Ermanno; Ermini, Luca; Fusco, Letizia; Pietrelli, Alessandro; De Bellis, Gianluca; Rollo, Franco; Luciani, Stefania (PloS one, 2014)
In the last years several phylogeographic studies of both extant and extinct red deer populations have been conducted. Three distinct mitochondrial lineages (western, eastern and North-African/Sardinian) have been identified reflecting different glacial refugia and postglacial recolonisation processes. However, little is known about the genetics of the Alpine populations and no mitochondrial DNA sequences from Alpine archaeological specimens are available. Here we provide the first mitochondrial sequences of an Alpine Copper Age Cervus elaphus. DNA was extracted from hair shafts which were part of the remains of the clothes of the glacier mummy known as the Tyrolean Iceman or Ötzi (5,350-5,100 years before present). A 2,297 base pairs long fragment was sequenced using a mixed sequencing procedure based on PCR amplifications and 454 sequencing of pooled amplification products. We analyzed the phylogenetic relationships of the Alpine Copper Age red deer's haplotype with haplotypes of modern and ancient European red deer. The phylogenetic analyses showed that the haplotype of the Alpine Copper Age red deer falls within the western European mitochondrial lineage in contrast with the current populations from the Italian Alps belonging to the eastern lineage. We also discussed the phylogenetic relationships of the Alpine Copper Age red deer with the populations from Mesola Wood (northern Italy) and Sardinia.